Pontine tegmentum hematoma: report of a case with pure hemiplegia - MILAGRES ANTONIO CARLOS DE PÁDUA; ALÓE FLÁVIO; LIMONGI JOÃO CARLOS PAPATERRA (Arquivos de Neuro-Psiquiatria)
The authors report the case of a 50 year-old hypertensive male patient with a pontine hematoma. The clinical presentation was characterized by pure pyramidal deficit signs (no other signs or symptoms were present). A pure hemiplegia syndrome, although common in supratentorial lesions, is considered to be a rare event in pontine vascular lesions. The pathophysiologic mechanisms of these neurological findings are unclear. The exclusive involvement of the pyramidal tract in this case is likely due to a variation in the vascular anatomy of the pons but, in some cases, a vascular malformation may be the cause.